Large-scale structure and the intrinsic alignment of galaxies. Issue Volume 11:Issue S308(2015) (12th October 2016) - Blazek, Jonathan; Seljak, Uroš; Mandelbaum, Rachel
Abstract: Coherent alignments of galaxy shapes, often called"intrinsic alignments" (IA), are the most significant source of astrophysical uncertainty in weak lensing measurements. We develop the tidal alignment model of IA and demonstrate its success in describing observational data. We also describe a technique to separate IA from galaxy-galaxy lensing measurements. Applying this technique to luminous red galaxy lenses in the Sloan Digital Sky Survey, we constrain potential IA contamination from associated sources to be below a few percent.